ANALISIS PEMETAAN MUTU PENDIDIKAN SMP NEGERI 3 BOJA KABUPATEN KENDAL - Mudzdalifah Mudzdalifah; Titik Haryati (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research aims to describe the mapping analysis of the quality of education at SMP Negeri 3 Boja, Kendal Regency. The research approach used is qualitative. This type of research is a case study. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The results of the research show that: Mapping the quality of education at SMP N 3 Boja, Kendal Regency, is very important to know the extent of the quality of education at the school. However, the analysis results show that the mapping method used still has shortcomings. Mapping focuses too much on academic achievement alone and pays little attention to other important things such as innovative learning methods, as well as specific problems faced by schools.